ENTREPRENEURSHIP IN COLLECTIONS: CHALLENGES AND OPPORTUNITIES IN MANAGING DIVERSIFIED CLIENT PORTFOLIOS - Neves Filho, Alexandre Wagner Barbosa (Revista Sistemática, 2020)
Entrepreneurship in the collections industry presents a complex interplay of challenges and opportunities shaped by regulatory requirements, ethical concerns, technological advancements, and the dynamics of managing diversified client portfolios. Entrepreneurs in this sector must navigate compliance with strict debt collection laws while simultaneously differentiating themselves through professionalism and trust-based relationships. At the same time, opportunities emerge from outsourcing trends, technological innovation, and the demand for specialized receivables management across industries. This paper analyzes the entrepreneurial journey within collections by exploring the difficulties of operating multiple firms, addressing sector-specific client needs, and overcoming resource constraints. Drawing on literature from entrepreneurship, financial management, and service innovation, the study highlights the importance of dynamic capabilities, strategic networking, and investment in digital platforms. The findings suggest that entrepreneurs who combine ethical practices, adaptive strategies, and innovative technologies can establish competitive advantages and transform collections into a strategic resource for financial sustainability.